Role of anti-vimentin antibodies in renal transplantation - Besarani, Dler; Cerundolo, Lucia; Smith, John D; Procter, Jeanette; Barnardo, Martin C N; Roberts, Ian S D; Friend, Peter J; Rose, Marlene L; Fuggle, Susan V (Transplantation, 2014)
The role of non-HLA antibodies in rejection is not clear. We investigate whether antibodies to vimentin are made after renal transplantation and if production is associated with interstitial fibrosis and tubular atrophy (IFTA). In this retrospective study, sera from 70 recipients of renal allografts (40 controls, 30 IFTA) were studied. The biopsy diagnosis of interstitial fibrosis and tubular atrophy (IFTA) was based on random, cause-indicating biopsies. Sera were collected pretransplant and at 3 monthly intervals up to 5 years posttransplant or diagnosis of IFTA and assayed by ELISA for IgM and IgG anti-vimentin antibodies (AVA) and HLA antibodies. Mean titers of IgM AVA were higher at every year after transplantation compared with pretransplant for both IFTA and controls groups (P<0.001). There was no difference in the mean level of IgM AVA achieved by IFTA and control groups. The mean pretransplant levels of IgG AVA in the IFTA and control group were 18.2±11.7 and 11.0±8.1, respectively (P=0.001). There was a significant increase between the pretransplant mean levels of IgG AVA and the levels at years 1 to 4 in the IFTA group (years 1-3, P<0.0001, year 4 P=0.003) but not in the controls. There was no significant difference between the numbers of IFTA or control patients achieving a positive value (mean+2SD of pretransplant antibody titers) of IgM AVA (50% versus 37.5%, respectively) or IgG AVA (26.6% versus 12.5%, respectively). There was no association between production of HLA and AVA antibodies. Posttransplant production of IgM AVA is not associated with IFTA. The production of IgG AVA by a minority of IFTA patients suggests that in some individuals, IgG AVA may be involved in the pathology of IFTA.